Preparation of TEM samples of ferritic alloys. - Yao, Z; Xu, S; Jenkins, M; Kirk, M (2008)
We describe techniques for electropolishing irradiated ferritic specimens for examination under the TEM in situations where the foil quality is of utmost importance. First, we describe some modifications to the standard technique for making plan-view specimens aimed at optimizing the foil quality. Second, we describe a technique for making plan-view specimens from a region of buried damage in a specimen irradiated with 2 MeV Fe(+) ions.